Efisiensi Teknis dan Ekonomis Pada Usahatani Padi di Desa Alang-alang Kecamatan Tragah Kabupaten Bangkalan - Ahdiningtyas, Meliana; Maidatatia, Al; Fitri, Shelian; Uyun, Sofiatul; Alwi, Fitriyah (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2022)
This study aims to analyze the level of technical, allocative and economic efficiency of farmers in Alang-Alang village towards rice farming, and to determine the factors that affect production efficiency. This research was conducted in Alang-Alang Village, Tragah District, Bangkalan Regency, the determination of this location was carried out purposively or intentionally. The number of respondents used in this study were 40 respondents using the Accidental Sampling technique. Analysis of the data used is in the form of an analysis of the stochastic frontier production function which is estimated by the maximum likelihood (MLE) method using the Frontier 4.1 program. Based on the results of the study, it can be shown that the level of technical efficiency of rice commodities in Alang-Alang Village, Tragah District, Bangkalan Regency is 0,73 (efficient enough), economic efficiency is 0,324 (not efficient), and allocative efficiency is 0,46 (not efficient). Factors or variables that significantly influence and have a positive value on rice production are labor. The source of technical inefficiency that has a significant and negative value is age. So that in maximizing rice production, farmers must increase the number of workers in their farming activities.